The Addition of Ferritin Enhanced the Prognostic Value of International Prognostic Index in Diffuse Large B‐Cell Lymphoma - Shen, Ziyuan; Zhang, Shuo; Zhang, Meng; Hu, Lingling; Sun, Qian; He, Chenlu; Yan, Dongmei; Ye, Jingjing; Zhang, Hao; Wang, Ling; Gu, Weiying; Miao, Yuqing; et al. (Frontiers in Oncology, 2022)
Diffuse large B-cell lymphoma (DLBCL) is a highly heterogeneous non-Hodgkin lymphoma, and the prognosis of DLBCL patients is widely affected by multivariables. Clinical-factors-based prognostic systems stratify the prognosis of DLBCL with certain limitations, and the value of ferritin on the prognosis of DLBCL is unclear. In this study, 225 cases were retrieved from 4 centers of Huaihai Lymphoma Working Group (HHLWG) as the derivation cohort, and 66 cases were from the other 6 centers of HHLWG as external validation cohort. X-Tile program divided ferritin into three groups when applying 175.00 and 391.90 μg/L as the optimal cutoff points. Based on multivariable analysis, ferritin appeared to be a stronger predictor. A total of three variables (ferritin, age, and lactate dehydrogenase) were included for the development of the nomogram. The C-indexes were 0.73 and 0.70 in the derivation and validation cohort, and the calibration curve showed the consistency between the nomogram prediction and the actual observation. In conclusion, Ferritin-based nomogram enhanced the prognostic value of IPI in DLBCL.